Effect of cold deformation on the hydrogen permeation in a dual-phase advanced high-strength steel. (20th August 2022) - Li, Huixing; Venezuela, Jeffrey; Zhou, Qingjun; Shi, Zhiming; Dong, Futao; Yan, Ming; Knibbe, Ruth; Zhang, Mingxing; Atrens, Andrej
Highlights: Permeation in DP1180 was investigated using electrochemical permeation. Cold deformation decreased the effective hydrogen diffusion coefficient. Cold deformation significantly increased the diffusible hydrogen concentration. Both effects were caused by hydrogen trapping. Abstract: The diffusion behaviour of hydrogen in a 1180 MPa ferrite/martensite dual-phase (DP) advanced high-strength steel was investigated using electrochemical permeation tests in the following conditions: as manufactured, cold deformed and annealed. The effective hydrogen diffusion coefficient (0.46 × 10 −6 cm 2 s −1 ) for the cold-deformed DP1180 was considerably lower than for the steel as-received (0.74 × 10 −6 cm 2 s −1 ) and annealed (2.2 × 10 −6 cm 2 s −1 ). The increased diffusible hydrogen concentration by cold deformation was attributed to increased reversibly trapped hydrogen. This work provides an experimental underpinning for the increased hydrogen embrittlement sensitivity caused by plastic deformation of the steel.